Neuromodulators in Men - Minokadeh, Ardalan; Matarasso, Seth L; Jones, Derek H (Dermatologic surgery, 2024)
Botulinum toxin treatment is gaining popularity among men for cosmetic purposes driven by workplace competition and a desire for confidence and youthfulness. Because of the unique features of male facial anatomy, careful consideration is necessary during assessment and treatment execution. The peer-reviewed literature on male facial anatomy in relation to neuromodulator treatment was analyzed with a particular emphasis on studies involving male subjects and the use of botulinum toxin type A. Anatomic differences in muscle mass and contraction patterns between men and women help guide treatment. Men appear to require higher doses for effective treatment of facial wrinkles and, in the case of glabellar lines, often require double the standard dose for women. Treatment of the frontalis muscle in men, responsible for forehead creases, requires precise dosage and placement to avoid brow ptosis. The lateral canthal wrinkles are often the first area that men seek consultation for. Although FDA approval for lower face regions is lacking, off-label use can still be considered. Successful botulinum toxin treatment in men necessitates understanding facial anatomy, customized treatment plans, and appropriate dosing. Further research is warranted to refine protocols and enhance outcomes for male patients.